Conceptual Model of Differentiated Social and Economic Policy of Smart Specialization of Regions - Serogina, Daria; Bazetska, Hanna (International Journal of Economics and Financial Issues, 2018)
In this article the methodical foundations for the construction of a regional innovation strategy and the vectors for the formation of a new policy are presented. The necessity of conducting a regionally differentiated innovation policy based on the principles of Smart Specialization is substantiated; the assessment of Ukraine’s preparedness for the practical implementation of the Smart Specialization concept is given. The authors consider the prerequisites for the application of the Smart Specialization concept in the EU and Ukraine; they also evaluate and formulate the advantages of applying the Smart Specialization strategy. When using the concept of Smart Specialization, the strategic directions are: creation and development of creative regions; development of a network of technologically advanced public services; assistance in the development of the infrastructure of the innovation ecosystem; encouraging small and medium-sized enterprises to participate in the global structure of value creation. We think that the application of the policy of the Smart Specialization of the regions will allow us to launch the process of improvement and transformation of national and regional innovative strategies that provide a strategic framework for innovative transformation of the regional economy and determine the main investment priorities. Keywords: Smart Specialization; regional development, innovation policy; economic growth, cluster policy. JEL Classifications: O33, O38, R11, R58